Atomic force microscopy and polarized Raman spectroscopy of (GaP)(n)/(InP)(n) short-period supeflattice structures - Lim, Jung-Ran; Rho, Heesuk; Song, J. D.; Choi, W. J.; Lee, Y. T. (KOREAN PHYSICAL SOC, 2008)
We report atomic force microscope (AFM) and polarized Raman scattering studies of (GaP)(n)/(InP)(n) (n = 1, 1.7, 2) short-period superlattice (SPS) structures. The AFM images obtained from the top surfaces of the n = I and 2 samples grown at 425 degrees C show planar surfaces. In contrast, the AFM image obtained from the n = 1.7 sample grown at 425 degrees C shows island features on the surface, suggesting that irregular lateral composition modulation (LCM) is present in this material. AFM studies of the samples grown at 490 degrees C indicate the presence of regular LCM for the n = 1 sample and irregular LCM for the n = 1.7 and 2 samples. Polarized Raman spectra from the SPS samples exhibit strong deviations from the cubic zincblende symmetry when LCM is present. The deviations of the polarization selection rules from cubic symmetry in the presence of irregular LCM are much larger than those in the presence of regular LCM.
Keywords: LATERAL COMPOSITION MODULATION; MOLECULAR-BEAM EPITAXY; SUPERLATTICE; ANISOTROPY; (GAIN)P; GAINP2; MODES